Age of Onset Moderates the Association between Total Antioxidant Capacity and Cognitive Deficits in Patients with Drug-Naïve Schizophrenia - Jiaxin Li; Deyang Li; Junru Guo; Dongmei Wang; Xiangyang Zhang (MDPI AG, 2023)
Schizophrenia patients with an earlier age of onset have been found to have more serious negative symptoms and cognitive deficits. Oxidative stress is thought to be implicated in cognitive impairment in schizophrenia. Total antioxidant capacity (TAOC) is an essential indicator of oxidative stress. However, the association between age of onset, TAOC, and cognitive performance in schizophrenia remains unexplored. In this study, 201 patients (age: 26.5 ± 9.6 years; male: 53.2%) with drug-naïve schizophrenia were recruited. Clinical symptoms were evaluated using the Positive and Negative Syndrome Scale (PANSS). Cognitive functioning was assessed using the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). Plasma TAOC levels were analyzed using established procedures. Results showed that early-onset (EO) patients had higher TAOC levels, more severe negative symptoms and performed worse on visuospatial/constructional, language and RBANS total scores than non-EO patients. After Bonferroni correction, only non-EO patients showed a significant inverse relationship between TAOC levels and RBANS language, attention, and total scores. Our findings suggest that an early/late age of onset may be correlated with psychopathological symptoms, cognitive impairment and oxidative responses in schizophrenia. Furthermore, the age of onset may moderate the relationship between TAOC and cognitive function in patients with schizophrenia. These findings suggest that improving oxidative stress status in non-EO schizophrenia patients may enhance their cognitive function.